QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY: AN EXPERIMENTAL RESEARCH ON STUDENTS’ READING COMPREHENSION - Lokot Lokot; wiki tedi rahmawati; Yunita Mutiara Harahap (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The objective of this research was to find out the effect of QAR strategy towards reading comprehension on descriptive text. Experimental design was applied in this research. The population and sample of this research were the eighth grade students of SMP Swasta Dwi Tunggal Tanjung Morawa with total number of students was 60. Class VIII-A was the experimental class and class VIII-B was the control class. Each class consisted of 30 students. The cluster random sampling with lottery technique was applied to decide the sample group. The instrument of collecting the data was multiple choice tests consisted of 30 items. To obtain the reliability of the test, Kuder Richardson 21 (KR-21) formula was applied and Biserial Point Correlation formula was used to calculate the validity. The t-test was used for the data analysis and it was obtained that t-observed (8.601) was higher than t-table (2.001) with level of significance 0.05 and df = 58. The hypothesis testing proved that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Thus, it was concluded that the Question Answer Relationship (QAR) Strategy significantly affected the students’ reading comprehension on descriptive text.